TAFSĪR AL-QURAN DENGAN AL-QURAN - Amin Songgirin (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2021)
This paper describes the interpretation of the Koran with the Koran which is the earliest method of interpretation to emerge and develop. The interpretation of the Qur'an with the Qur'an is one type of interpretation bi al-ma'thūr which includes the interpretation and the interpreter. This type of interpretation is not filled with falsehood, because the source is directly from Allah SWT. The method used in this paper is descriptive analytic method. The interpretation of the Qur'an with the Qur'an uses several methods; Mujmal and Mubayyan (al-Ijmāl wa al-Bayān); Al-Muṭlaq and al-Muqayyad; Takhṣīṣ al'-Ām; Al-Bayān bil-Manṭūq aw bil-Mafhūm; Tafsr Lafzi bi-Lafzi; Tafsr Ma'nā with Ma'nā; Tafsr Uslūb fī yatin bi Uslbi fī yatin al-Ukhrā; Tabyīn al-Mūjaz bil-Mufaṣal; Al-jam'u Baina mā Yatawahhama Annahu Mukhtalif.